Oil yield of green microalgae isolated from ponds around Banda Aceh City - . Marwan; . Suhendrayatna; . Bahagia (Syiah Kuala University, 2011)
Study on CO2 fixation for the growth of oil-produced green microalgae by cultivating the algae in illuminated glass containers was conducted. Green algae were isolated from some water pond samples around Banda Aceh. The samples contain mixed biomasses. The types of microalgae, as the results of the isolation was identified, and then cultivated in the CO2 bubbled containers. The algae growth and oil yield were observed under different mediums (modified Detmer and modified CHU-13) and illumination (2 x 8 watts and 4 x 8 watts). Tanjong Selamat samples were used throughout this research based on initial screening stage. The two medium used led to different growths of the algae; the Detmer medium giving higher growth rate. Faster growth rates were found for cultivation using modified Detmer medium and 4 x 8 watts illumination. The oil yield was determined by solvent extraction method. Oil yield using the CHU-13 medium was 88.5%, much higher than the yield of Detmer medium sample 55.4%. It shows the potential use of local green microalgae to produce alternative bio-oil.